Trunk mobility in the sagittal and horizontal planes: Clinical methods to quantify movement in an elite surfing population - Furness, J.; Climstein, M.; Sheppard, J. M.; Abbott, A. (Physical Therapy in Sport, 2016)
High numbers of acute shoulder and chronic lumbar injuries have been identified in a surfing population. A simple screening tool could be used to determine whether thoracic spine dysfunction is a possible contributor to shoulder or lumbar injuries. Importantly, thoracic mobility in the sagittal and horizontal planes are key requirements in the sport of surfing; however to date the normal values of these movements have not yet been quantified in a surfing population.